Reduction of cerebral DWI lesion burden after carotid artery stenting using the CASPER stent system. (21st June 2018) - Broussalis, Erasmia; Griessenauer, Christoph; Mutzenbach, Sebastian; Pikija, Slaven; Jansen, Hendrik; Stevanovic, Valdo; Killer-Oberpfalzer, Monika
Abstract : Introduction: Despite various measures to protect against distal embolization during carotid artery stenting (CAS), periprocedural ischemic lesions are still encountered. Objective: To evaluate the periprocedural cerebral diffusion weighted imaging (DWI) lesion burden after CASPER stent placement. Methods: Patients who underwent CAS using the CASPER stent system were reviewed. Degrees of carotid stenosis and plaque configuration were determined. All patients were pretreated with dual antiplatelet agents and cerebral pre- and postprocedural MRI was obtained. All CAS procedures were performed by a single operator. Results: A total of 110 patients with severe carotid artery stenosis (median degree of stenosis 80%, median length of stenosis 10 mm) were treated with CAS. Hypoechogenic or heterogeneous, mostly hypoechogenic, plaques were documented in 48.6% (52/107) of patients. Carotid ulceration was present in 15.9% (17/107). Postprocedurally, 7.3% (8/110) of patients were found to have ischemic DWI lesions. They were asymptomatic in all patients. Follow-up at 90 days was available in 88.2% (97/110) of patients with excellent functional outcome (modified Rankin Scale score 0–1) in 95.9% (93/97). Conclusion: Carotid artery stenting using the new CASPER stent in combination with a distal embolic protection device is safe and results in a lower rate of periprocedural DWI lesion burden compared with reported results for historic controls.